How do orthoses impact ease of donning, handwriting, typewriting, and transmission of manual torque? A study of three prefabricated wrist-hand orthoses - Ferrari, Ana Lya M. [UNESP]; Medola, Fausto O. [UNESP]; Sandnes, Frode E. (Wolters Kluwer, 2021)
Introduction: Many upper-limb injuries have work-related causes such as continued use of computers, typing activities, mouse manipulation, and repetitive movements performed for long periods. This study evaluated the performance of wrist-hand orthoses in manual tasks and in transmission of torque measurement during canned glass opening. Methods: Thirty healthy participants performed donning, typing, and handwriting tasks and transmission of manual torque. The procedures were performed in four conditions: with three different orthoses and with no orthosis as a control. Results: The results showed a significant difference in the time of manual writing (P < 0.001) and in the number of words per minute (P < 0.001) in the typing task with and without orthoses. The perceived difficulty in performing typing (P < 0.001) and manual writing (P < 0.001) was lower with no orthoses and higher for canvas orthosis and the two neoprene orthoses. Transmission of manual torque also decreased with the orthoses compared with using no orthosis (P < 0.001). Among the orthoses, the canvas fabric orthosis yielded a lower performance compared with the two different neoprene fabric orthoses for all the tasks. Conclusions: There are effects of the materials used and the orthosis design when performing handwriting typing tasks and twisting tasks (transmission of manual torque), as well as the correctness of how users donned the orthosis.
Keywords: Orthotic devices; Upper limb; Wrist injuries